Changes in three-dimensional magnetic fields of star shaped JIS-SKS93 plates embedded in clear acrylic cold mounting resin under tensile loads. (March 2014) - Kida, K.; Uryu, M.; Honda, T.; Costa Santos, E.
Abstract : In order to understand the relationship between the phenomena of stress concentration and failure, non-destructive evaluation methods using in situ measurements in the stress concentration areas are necessary. In the present work, the three-dimensional magnetic fields were observed at room temperature in air using a scanning Hall probe microscope. The effect of stress on the changes in the magnetic field in complex shaped steel components is reported. A star shaped steel plate (JIS SKS93) embedded in acrylic resin was strained at different loads without any influence from the ferromagnetic machine system and the magnetic fields before and after straining were observed. The obtained magnetic images clearly corresponded with the star shape of the steel plate. It was possible to measure the changes in the magnetic field of the complex shaped steel sample after straining under tensile loading.